Factor Structure and Initial Validation of a Multidimensional Measure of Difficulties in the Regulation of Positive Emotions: The DERS-Positive. (May 2015) - Weiss, Nicole H.; Gratz, Kim L.; Lavender, Jason M.
Emotion regulation difficulties are a transdiagnostic construct relevant to numerous clinical difficulties. Although the Difficulties in Emotion Regulation Scale (DERS) is a multidimensional measure of maladaptive ways of responding to emotions, it focuses on difficulties with the regulation of negative emotions and does not assess emotion dysregulation in the form of problematic responding to positive emotions. The aim of this study was to develop and validate a measure of clinically relevant difficulties in the regulation of positive emotions (DERS-Positive). Findings revealed a three-factor structure and supported the internal consistency and construct validity of the total and subscale scores.